Proceedings of the International Conference on Social Science, Political Science, and Humanities (ICoSPOLHUM 2020) 2021
DOI: 10.2991/assehr.k.210125.009
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perception on Online Learning During the Covid-19 Pandemic

Abstract: This study examines the students' perceptions towards online learning at Universitas Malikusaleh in Lhokseumawe City during the Covid-19 pandemic. This study reviews the perceptions of students at this higher education institution about the online learning process during the Covid-19 pandemic. The study covered the learning process, learning environment, and learning motivation. The method used in this research is a quantitative approach where the researchers distributed a self-administered questionnaire consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 9 publications
0
7
0
2
Order By: Relevance
“…7 Likewise, Indonesia had less preference for online learning than face-to-face learning. 8 Students' perception is vital for introduction of online teaching-learning to keep the transmission of COVID-19 in check. This study aimed to explore the nursing students' perception of online learning during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…7 Likewise, Indonesia had less preference for online learning than face-to-face learning. 8 Students' perception is vital for introduction of online teaching-learning to keep the transmission of COVID-19 in check. This study aimed to explore the nursing students' perception of online learning during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the findings showed that they felt less anxious during online classes. In summary, the results of this study showed that online learning was less for students than face-to-face learning (Azhari, 2021).…”
Section: Discussionmentioning
confidence: 57%
“…En efecto, el paso de la presencialidad a la virtualidad no fue valorado positivamente por los estudiantes (Azhari y Kurniawati, 2021;Lovón et al, 2020;Tejedor et al, 2020). Las condiciones y cambios generaron este descontento en la población estudiantil.…”
Section: Desafíos De Los Estudiantes En La Pandemiaunclassified